2019
DOI: 10.1002/psp4.12442
|View full text |Cite
|
Sign up to set email alerts
|

Time‐to‐Event Modeling of Peripheral Neuropathy: Platform Analysis of Eight Valine‐Citrulline‐Monomethylauristatin E Antibody–Drug Conjugates

Abstract: Peripheral neuropathy (PN) is a common long‐term debilitating toxicity of antimicrotubule agents. PN was the most frequent adverse event resulting in dose modifications and/or discontinuation of treatment for valine‐citrulline‐monomethylauristatin E antibody–drug conjugates (ADCs) developed at Genentech. A pooled time‐to‐event analysis across eight ADCs (~700 patients) was performed to evaluate the relationship between the ADC exposure and the risk for developing a clinically significant (grade ≥ 2) PN. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Body weight was identified as a positive risk factor for PN after accounting for conjugate exposure. This finding is supported by another analysis in which the TTE model was expanded to include eight MMAE‐containing ADCs . It was reported that height, which is highly correlated with body weight, is an important and independent risk factor for PN .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Body weight was identified as a positive risk factor for PN after accounting for conjugate exposure. This finding is supported by another analysis in which the TTE model was expanded to include eight MMAE‐containing ADCs . It was reported that height, which is highly correlated with body weight, is an important and independent risk factor for PN .…”
Section: Discussionmentioning
confidence: 54%
“…This finding is supported by another analysis in which the TTE model was expanded to include eight MMAE-containing ADCs. 26 It was reported that height, which is highly correlated with body weight, is an important and independent risk factor for PN. 27 There is also a trend for higher risk with increasing serum albumin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Time-to-event modeling of peripheral neuropathy-platform modeling. 41 (A) Model structure. The hazard in the time-to-event model is driven by individually predicted antibody-drug conjugate plasma concentrations (Cp).…”
Section: Discussionmentioning
confidence: 99%
“…40 To assess risk factors for developing PN and to evaluate if drug target plays a role, a pooled time-to-event analysis across 8 vc-MMAE antibody-drug conjugates (∼700 patients) was performed to evaluate the relationship between the antibody-drug conjugate exposure and the risk for developing a clinically significant (grade ≥ 2) PN ( Figure 6). 41 The analysis suggested that the risk for developing PN was largely independent of target and cancer type but increased with antibody-drug conjugate exposure and treatment duration. In addition, large body weight and previously reported PN increased the risk for developing PN (Figure 6).…”
Section: Platform Pk/pd Modeling Of Antibody-drug Conjugatesmentioning
confidence: 99%
“…BW appears to be a PN risk factor independent of drug exposure, as the increased exposure in high BW patients given per mg/kg dose was not sufficient to explain the impact of BW on observed incidence of PN. As a result, the model simulation suggested that capping the dose for patients > 100 kg only had a marginal benefit for these patients in reducing the PN risk (20).…”
Section: Treatment Duration Cappingmentioning
confidence: 98%